The cheerleaders of doom / 3. - Buckley, Michael (Buckley, Michael. NERDS, 2012)
Matilda "Wheezer" Choi, an asthmatic who uses nanobyte-enhanced inhalers and hates anything girlie, must infiltrate the cheerleading squad when former member of NERDS turned villain, Gerdie Baker, becomes a cheerleader and starts pillaging other worlds with the assistance of a device the criminal mastermind Simon helped her make.